Interplay Between Macrophages and Angiogenesis: A Double-Edged Sword in Liver Disease - Ramirez-Pedraza, Marta; Fernández, Mercedes (Frontiers in Immunology, 2019)
During chronic liver disease, macrophages support angiogenesis, not only by secreting proangiogenic growth factors and matrix-remodeling proteases, but also by physically interacting with the sprouting vasculature to assist the formation of complex vascular networks. In the liver, macrophages acquire specific characteristics becoming Kupffer cells and working to ensure protection and immunotolerance. Angiogenesis is another double-edged sword in health and disease and it is the biggest ally to macrophages allowing its dissemination. Angiogenesis and fibrosis may occur in parallel in several tissues as macrophages co-localize with newly formed vessels and secrete cytokines, interleukins and growth factors that will activate other cell types in the liver such as hepatic stellate cells and liver sinusoidal endothelial cells, promoting extracellular matrix accumulation and fibrogenesis. Vascular endothelial growth factor, placental growth factor and platelet-derived growth factor are the leading secreted factors driving pathological angiogenesis and consequently increasing macrophage infiltration. Tumor development in the liver has been widely linked to macrophage-mediated chronic inflammation in which epidermal growth factor, STAT3 and NF-kβ are some of the most relevant signaling molecules involved. In this article, we review the link between macrophages and angiogenesis at a molecular and cellular level in chronic liver disease.